THE APPLICATION MODEL LEARNING GAMES ABC TO IMPROVE RESULT OF LEARNING - Azizah; Agnes Wanda Sari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The main problem in this study is the low student learning outcomes of class V on natural science subjects due the lack of creative students to solving problems in science learning. The idea of student focus on the material in recognized. This study aims to improve student learning outcomes of natural science subjects through the application of ABC Games learning models in fifth grade students of SDN Biro. This type of research is a classroom action research consisting of 2 cycles with stages of planning, implementation, observation and reflection. The subjects of this study were the fifth grade students of SDN Biro with a total of 22 students consisting of 7 male students and 15 female students. Data collection techniques used were teacher observation skills sheets, student activity observation sheets, and student learning outcomes tests in the form of multiple choice questions totaling 10 numbers. The results obtained in cycle 1 are the percentage of classical learning completeness 75%, the percentage of teacher skills 75.83%, and the percentage of student activities 73.33%. In cycle 2 the classical learning completeness obtained 85.71%, the percentage of teacher skills 85.83, and the percentage of student activity 85%. So it can be concluded that the application of ABC Games learning model can improve the learning outcomes of science subjects in Class V Students of SDN Biro seen from the increase in learning outcomes from cycle 1 to cycle 2.